GROWTH INHIBITION OF FUNGAL PLANT PATHOGENS BY ANTAGONIST BACTERIA USING DUAL CULTURE ASSAYS - Yan Ramona (SEAMEO BIOTROP, 2021)
There has been excessive use of chemical-based pesticides globally, resulting in significant environmental consequences with adverse effects on human health. Therefore, more sustainable and environmentally friendly alternative solutions are needed to counter such environmental and health challenges. Development of biocontrol methods is a sustainable solution to these challenges. The main objective of this research was to investigate the efficacy of potential antagonist bacteria to inhibit important fungal plant pathogens in vitro by applying dual culture assays on potato dextrose agar (PDA) or trypticase soya agar (TSA) media, with a view to isolate and screen potential antagonists for the development of future biocontrol agents. The target pathogens were Fusarium oxysporum, Ceratocystis sp., Aspergillus flavus, and Aspergillus niger, commonly found infecting horticultural plants in Bedugul Village in North Bali Island. The antagonist bacteria were isolated from various sources such as soil from the rhizosphere zone, roots of lettuce plants, and mature compost. The potential of antagonist candidates was screened on the basis of inhibitory activity against targeted fungal pathogens. Bacterial antagonists with the highest zones of inhibition were identified up to the genus level using biochemical tests, and the results were matched with those specified in Bergey’s Manual of Determinative Bacteriology. Fifteen bacterial isolates were successfully isolated from various sources, and 60% of these isolates showed antagonistic activity in vitro against fungal pathogens with varying degrees of inhibition. This indicated the initial potential for development as biocontrol agents. Based on preliminary identification, the genera Bacillus and Pseudomonas were found to be the predominant isolates, and in addition, the genus Acinetobacter was also identified in this study.